(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Childhood tuberculosis (TB) remains a major public health challenge, with more than 1 million cases estimated annually and a high proportion of “missed” diagnoses. Chest radiography (CXR) is the most widely used imaging modality for detecting pediatric pulmonary TB because of its ubiquity, speed, and low cost. Its interpretation, however, is complicated by age specific disease patterns, overlapping differentials, and reader variability. This narrative review synthesises contemporary evidence on the performance, pitfalls, and evolving role of CXR in the diagnosis of childhood TB, drawing on guidelines, systematic reviews, and recent innovations such as computer aided detection. We discuss radiographic manifestations across the disease spectrum, technical considerations that influence image quality, diagnostic accuracy relative to microbiological and advanced imaging benchmarks, and practical algorithms for low resource settings. We also explore radiation dose optimisation, capacity building for readers, and future directions, including AI enhanced triage and ultra low dose tomosynthesis. Tables and a flow diagram summarise key findings, and more than 40 primary sources are referenced to provide an academically robust platform for clinicians, radiologists, and programme managers seeking to improve paediatric TB care.